Case Report on the Use of a Custom Myoelectric Elbow–Wrist–Hand Orthosis for the Remediation of Upper Extremity Paresis and Loss of Function in Chronic Stroke. Issue 7 (1st July 2017) - Dunaway, Stefanie; Dezsi, D. Brianna; Perkins, Jessica; Tran, Daniel; Naft, Jonathan
ABSTRACT: Introduction: This case study describes the application of a commercially available, custom myoelectric elbow–wrist–hand orthosis (MEWHO), on a veteran diagnosed with chronic stroke with residual left hemiparesis. The MEWHO provides powered active assistance for elbow flexion/extension and 3 jaw chuck grip. It is a noninvasive orthosis that is driven by the user's electromyographic signal. Experience with the MEWHO and associated outcomes are reported. Materials and Methods: The participant completed 21 outpatient occupational therapy sessions that incorporated the use of a custom MEWHO without grasp capability into traditional occupational therapy interventions. He then upgraded to an advanced version of that MEWHO that incorporated grasp capability and completed an additional 14 sessions. Range of motion, strength, spasticity (Modified Ashworth Scale [MAS]), the Box and Blocks test, the Fugl–Meyer assessment and observation of functional tasks were used to track progress. The participant also completed a home log and a manufacturers' survey to track usage and user satisfaction over a 6-month period. Results: Active left upper extremity range of motion and strength increased significantly (both with and without the MEWHO) and tone decreased, demonstrating both a training and an assistive effect. The participant also demonstrated an improved ability to incorporate his affected extremity (with the MEWHO) into a wide variety of bilateral, gross motor activities of daily living such as carrying a laundry basket, lifting heavy objects (e.g. a chair), using a tape measure, meal preparation, and opening doors. Conclusion: Custom myoelectric orthoses offer an exciting opportunity for individuals diagnosed with a variety of neurological conditions to make advancements toward their recovery and independence, and warrant further research into their training effects as well as their use as assistive devices.